INCREASING AWARENESS OF FAMILY FAMILY THROUGH GUIDANCE OF THE SOCIODRAMA TECHNIQUE GROUP OF CLASS VIII-2 STUDENTS DWITUNGGAL PRIVATE SMP 2021/2022 ACADEMIC YEAR - Yu n i a s i h. S.Pd (CV. Asy Persada Quality, 2024)
The aim of this research is to increase awareness of closeness in the families of class VIII-2 students at Dwitunggal Private Middle School through the guidance of the Sociodrama Technique group. Counseling Guidance Action Research (PTBK). And the approach taken is a qualitative approach because this research seeks to increase students' awareness of the importance of closeness in the family. The research objects in this PTBK are students in class VIII-2 of Dwitunggal Private Middle School for the 2021/2022 academic year. Class determination is obtained based on the results of observations of the class to be studied. Furthermore, the guidance group was obtained based on Random Sampling Techniques and by paying attention to the results of the questionnaire. Meanwhile, the research subject is the guidance service of the Sociodrama technical group with 9 students. The results of research at the initial observation stage in administering questionnaires to 38 students showed that only 9 students had a low awareness of closeness in the family, each of which was in the sufficient category (51% -75%). The continued implementation of cycle II turned out to produce maximum results. In cycle II with two regular meetings, there was an increase in awareness of closeness within the family among students, this was shown by the results of the questionnaire which showed it was in the successful category (75% -100%). The conclusion that can be drawn from this research is that through group guidance sociodrama techniques can increase awareness of intimacy in the families of class VIII-2 students at Dwitunggal Private Middle School.